IDENTIFIKASI DEBIT LIMPASAN AIR PERMUKAAN KAWASAN GEDEBAGE SESUDAH PERUBAHAN IKLIM - MARSELLY DWIPUTRI (Faktor Exacta, 2017)
. The Primary Gedebage is the area of the floodplain. Some of the main elements that influence of flooding rainfall intensity is increasing every year due to climate change and changes in land use. To know the discharge of surface water runoff area Primary Center Gedebage, then carried out the identification of surface water discharge area Primary Center Gedebage. The purpose of the writing of this journal is to know the increased discharge of surface water runoff in the Primary Gedebage in year 2031. In the writing of this journal method does is quantitative descriptive method, while for the way the analysis will be performed using the method of rational analysis researchers. The results obtained are contained percentages of discharge runoff primary Center Gedebage area that is not supported by the primary drainage capacity of capacity currently. Based on the existing land use, seen that the percentage increase in the largest surface water runoff in year 2031 of 53% (132.05 m³/s), based on the land use plan, the percentage increase in the largest surface water runoff in year 2031 of 52% (137.78 m³/s), and the percentage increase in discharge due to climate change on the entire land use in the area of Gedebage with the impact of the highest percentage of 329% compared to primary current drainage infrastructure.